Genetic Polymorphisms on OPRM1, DRD2, DRD4, and COMT in Young Adults: Lack of Association With Alcohol Consumption - Chung, Patrick; Logge, Warren B.; Riordan, Benjamin C.; Haber, Paul S.; Merriman, Marilyn E.; Phipps-Green, Amanda; Topless, Ruth K.; Merriman, Tony R.; Conner, Tamlin; Morley, Kirsten C. (Frontiers in Psychiatry, 2020)
Background: Risk behaviours for emerging adults such as alcohol use are associated with increased risk of morbidity and mortality. Patterns of risk behaviour may be genetically determined and vary between genders. Previous studies have demonstrated that some genotypes may predict addictive behaviours including alcohol consumption and impulsivity, for example OPRM1 A118G, COMT Val158Met and DRD2 Taq1A and DRD4 C52IT. Methods: This study thus aimed to investigate the predictive relationship of these four single nucleotide polymorphisms (SNPs) on student patterns of drinking using a micro-longitudinal daily diary design in a sample of 628 young adults ages 18 – 25 of predominantly of European ethnicity. Linear mixed models were used to examine the effect of SNPs on the number of drinks per drinking session with gender as a moderating variable. Results: There were no main effects for genotype on alcohol consumption, nor for gender x genotype for any of the SNPs. There was a trend for an effect of the DRD2 Taq1A on the number of drinks per drinking day and for the interaction of gender and DRD2 Taq1A on the number of drinks per drinking day. Conclusion: These findings suggest that the DRD2 Taq1A, OPRM1 A118G, DRD4 C521T or COMT Val158Met polymorphisms, are not associated with alcohol consumption in emerging adults, although there may be a relationship between DRD2 Taq1A and alcohol consumption in males.